Al-Mg electrodeposition using chloride-based molten salts - Sreesvarna Bhaskaramohan; M. J. N. V. Prasad; G. V. Dattu Jonnalagadda; Sankara Sarma Tatiparti (Journal of Electrochemical Science and Engineering)
Al-Mg alloys were potentiostatically electrodeposited from electrolyte with AlCl3, NaCl, KCl and MgCl2 at 180 °C for aircraft applications. The electrode setup includes a Cu cathode, Pt-mesh anode, and Al-rod pseudo-reference electrode. Cyclic voltammetry (CV) reveals the Al deposition sources as Al2Cl7-and AlCl4-. The Mg deposition source can be a reaction between Al2Cl7- and MgCl2 and MgCl2 dissociation (both releasing Mg2+). Depositions at overpotentials: -1.03, -1.05, -1.06, and -1.10 V show current density-time curves with almost steady-state j, indicating planar diffusional growth. This is confirmed by layer-like morphologies with near-globular growth features. The average feature size decreases to -1.06 V and increases slightly at -1.10 V due to further deposition over the existing features. The deposit composition (Mg content) increases from 0.36 to 5.68 at.% from -1.03 to -1.10 V. Such a wide range of Mg content is obtained through minimal compositional changes in spent electrolytes, indicating the ease of less-noble Mg deposition. Al-Mg deposition scheme is devised with Al and Mg deposition perceived as Al3+ + 3e-  Al and Mg2+ + 2e-  Mg; and 2Cl- Cl2(↑)+ 2e- supplying electrons for deposition.